2003
DOI: 10.1007/s10350-004-6533-1
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Difficile Infection—An Unusual Cause of Refractory Pouchitis: Report of a Case

Abstract: infection can complicate pouchitis in patients with an ileal pouch-anal anastomosis and should be considered in patients who fail to respond to standard treatment, including metronidazole. In cases of refractory pouchitis, superadded infection with should be excluded before initiation of potent anti-inflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 17 publications
0
37
0
3
Order By: Relevance
“…Mann et al [7] reported the first case of Clostridium difficile-associated pouchitis. A 35-year-old female patient with chronic refractory pouchitis was found to have Clostridium difficile infection while on metronidazole and prednisone.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mann et al [7] reported the first case of Clostridium difficile-associated pouchitis. A 35-year-old female patient with chronic refractory pouchitis was found to have Clostridium difficile infection while on metronidazole and prednisone.…”
Section: Discussionmentioning
confidence: 98%
“…Clostridium ina propria is normocellular, and the villous architecture is intact. The crypts are also regularly distributed difficile is a common nosocomial pathogen responsible for most cases of pseudomembranous colitis and up to 20% of cases of antibiotic-associated diarrhea [7]. Clostridium difficile is prone to colonize the colonic mucosa, but occasionally colonize the mucosa of the small bowel [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 An unusual feature in the case that we describe is the nodularity seen at flexible sigmoidoscopy. This is not a typical finding in C. difficile-associated colitis; diffuse inflammation and pseudomembranes are more commonly seen.…”
Section: Discussionmentioning
confidence: 86%
“…It is important to investigate why patients do not respond to antibiotic therapy. Possible reasons include NSAID use, 33 concurrent C. difficile 34 or CMV infection, 35,36 celiac disease, cuffitis, and CD. After the exclusion of these factors, there are several treatment options.…”
Section: Discussionmentioning
confidence: 99%